Characterization of Udaipuri goat in its native tract - R.S. Barwal,; C.V. Singh,; Shailendra Singh, (Journal of Livestock Biodiversity, 2025)
The name Udaipuri of this breed has its genesis from Udaipuri Patti, where it actually originated and reared in largenumbers by the inhabitants of the area. The breed is distributed from Dugadda to Devrana area of Rathwadhasranges (Dugadda to Kandi ridge) of Pauri Garhwal district. In kids, the mean horn length, forehead length, earlength, height at withers, body length, chest girth, tail length and body weight from 0-3 months of age were0.64±0.05 cm, 8.77±0.05 cm, 10.14±0.06 cm, 33.41±0.11 cm, 31.64±0.12 cm, 36.64±0.11 cm, 7.84±0.05 cm and2.48±0.04 kg, respectively in females and 1.26±0.08 cm, 8.95±0.07 cm, 9.84±0.09 cm, 35.84±0.12 cm, 35.0±0.14cm, 38.58±0.13 cm, 8.12±0.06 cm and 2.79±0.06 kg, respectively in males. The average body measurement at adultage for horn length, forehead length, ear length, height at withers, body length, chest girth, tail length were16.05±0.05 cm, 15.97±0.03 cm, 14.73±0.03 cm, 62.03±0.06 cm, 61.21±0.06 cm, 71.21±0.07 cm and 12.76±0.03 cm,respectively in males and 12.17±0.01 cm, 15.09±0.01 cm, 14.44±0.01 cm, 59.10±0.01 cm, 60.82±0.01 cm,70.96±0.01 cm and 11.87±0.01 cm, respectively in females. The Udaipuri goats are small in size with 22.10±0.01 kgbody weight of adult females and 24.67±0.07 kg of body weight of males. The marketing of live animal is organizedand trading or prices are decided on live body weight bases.